2019
DOI: 10.1051/matecconf/201926201002
|View full text |Cite
|
Sign up to set email alerts
|

Riverbed transformation as a result of a ferry crossing construction – case study

Abstract: Riverbed under the influence of natural and anthropogenic factors is constantly being transformed. The changes of the channel parameters related to natural phenomena are rarely dynamic. Contrarily it is in the case of human activity. The introduction of river engineering structures to the riverbed aims to quickly adapt the river to the requirements. If construction of such forms is designed taking account of natural conditions prevailing in the riverbed, then negative effects cannot be observed. The situation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…There is only one exception, on the right bank along the bow downstream the crossing, the process of bank erosion was observed. As it was stated in [18], the right bank of the channel has moved around 270 m (from 1959 to 2003). In the second localization (Brzumin), slight changes in shorelines along the section are visible as well.…”
Section: Resultsmentioning
confidence: 83%
“…There is only one exception, on the right bank along the bow downstream the crossing, the process of bank erosion was observed. As it was stated in [18], the right bank of the channel has moved around 270 m (from 1959 to 2003). In the second localization (Brzumin), slight changes in shorelines along the section are visible as well.…”
Section: Resultsmentioning
confidence: 83%
“…For example, it was shown that the channel's narrowing due to the construction of a ferry crossing caused intensive sedimentation downstream of the narrowing in the expansion zone. In contrast, bank erosion and the channel bar strengthening outwash were observed under other flow conditions [59]. The analyses indicate that hydropower plants can also influence the river's hydromorphological conditions, although their impact is ambiguous.…”
Section: Plos Onementioning
confidence: 78%
“…The final index values are then calculated using specific formulas. The score obtained from the calculation (0-100) is compared to the five-point NSFWQI rating scale excellent (91-100), good (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90), moderate (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70), low and bad (0-25), [93,94]. Another index commonly used in river assessment is the Water Pollution Index (WPI).…”
Section: Plos Onementioning
confidence: 99%